+0  
 
0
468
2
avatar

Simplify(-5+q)(-4p)-(-3q)(-3p-2)

 Jun 13, 2017
 #1
avatar+7373 
+1

\((-5+q)(-4p)-(-3q)(-3p-2)\\ =(20p-4pq)-(9pq+6q)\\ =20p-6q-13pq\)

Edited: Did something wrong. sry.

.
 Jun 13, 2017
edited by MaxWong  Jun 13, 2017
 #2
avatar+21869 
+1

Simplify(-5+q)(-4p)-(-3q)(-3p-2)

 

\(\begin{array}{|rcll|} \hline && (-5+q)(-4p)-(-3q)(-3p-2) \\ &=& (5-q)(4p)+(3q)(-3p-2) \\ &=& 20p-4pq -9pq - 6q \\ &=& 20p-13pq - 6q \\ \hline \end{array}\)

 

 

laugh

 Jun 13, 2017

33 Online Users

avatar
avatar
avatar
avatar
avatar
avatar